A Volunteer Program to Connect Primary Care and the Home to Support the Health of Older Adults: A Community Case Study - Oliver, Doug; Dolovich, Lisa; Lamarche, Larkin; Gaber, Jessica; Avilla, Ernie; Bhamani, Mehreen; Price, David (Frontiers in Medicine, 2018)
Primary care providers are critical in providing and optimizing health care to an aging population. This paper describes the volunteer component of a program (Health TAPESTRY) which aims to encourage the delivery of effective primary health care in novel and proactive ways. As part of the program, volunteers visited older adults in their homes and entered information regarding health risks, needs and goals into an electronic application on a tablet computer. A total of 657 home visits were conducted by 98 volunteers, with 22.45% of volunteers completing at least 20 home visits over the course of the program. Information was summarized in a report and electronically sent to the health care team via clients’ electronic medical records. The report was reviewed by the interprofessional team who then plan ongoing care. Volunteer recruitment, screening, training, retention and roles are described. This paper highlights the potential role of a volunteer in a unique connection between primary care providers and older adult patients in their homes.